Spiritual Brotherhood of Mandaling Ethnic Groups Abroad through Tarekat Naqshabandiyah Khalidiyah Jalaliyah (TNKJ) - Lubis, Zakaria Husin; Romadona, Ihza; Harahap, Jamiatul Hasanah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study investigates the transformation of spiritual practices among the Mandailing Muslim community in urban Indonesia, focusing on their use of the Naqshbandi Khalidiyah Jalaliyah order as a means of sustaining ethnic identity while abroad. Employing a qualitative phenomenological approach, data were collected through field observations, in-depth interviews with spiritual leaders, and document analysis in key urban centers, namely Jakarta, Bandung, Bogor, Depok, Tangerang, and Bekasi. The findings reveal that global modernization processes and migration dynamics have induced a shift from universal Sufism toward an ethnically rooted spiritualism, primarily driven by the Mandailing community. This phenomenon strengthens intra-ethnic bonds via spiritual practices inspired by Dalihan Na Tolu, fostering community cohesion amidst cultural assimilation challenges. The study offers concrete evidence that religious practices adapt to socio-cultural contexts, illustrating how ethnicity influences spiritual life in migration settings. Its contribution lies in illuminating the intersection of religion, ethnicity, and social resilience in contemporary Indonesia, providing valuable insights for scholars in religious studies, anthropology, and diaspora studies concerning the role of local cultures in shaping spiritual expressions in urban environments.